Two-step flash sintering of ZnO: Fast densification with suppressed grain growth. (December 2017) - Nie, Jiuyuan; Zhang, Yuanyao; Chan, Jonathan M.; Jiang, Sicong; Huang, Rongxia; Luo, Jian
Abstract: Two-step flash sintering (TSFS) was proposed as a new ceramic fabrication method to achieve fast densification with suppressed grain growth. Using ZnO as an examplar, ~ 96.5% of theoretical density was achieved using TSFS with a grain size of ~ 370 nm, representing a > 3 times reduction of the grain size in comparison with conventional (one-step) flash sintering. Moreover, TSFS achieved this result in a few minutes, > 200 times faster than that needed for conventional two-step sintering to obtain comparable results, thereby representing an opportunity for significant energy and cost savings. Graphical abstract: